Pengaruh Work Life Balance terhadap Kinerja Karyawan melalui Komitmen Organisasi pada PT. X - Ghinathaya Julia Berliana; Agus Frianto (Universitas Negeri Surabaya, 2026)
This study aims to analyze the effect of work life balance on employee performance through organizational commitment. This research uses a quantitative approach with a sample of 50 employees of PT. X Surabaya. Data were collected using a questionnaire measured with a Likert scale. The data analysis technique used was Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0 software. The results show that work life balance has a positive and significant effect on employee performance, work life balance has a positive and significant effect on organizational commitment, organizational commitment also has a positive and significant effect on employee performance, and organizational commitment was not able to mediate the relationship between work life balance and employee performance. These findings indicate that employee performance is more directly influenced by work life balance than through organizational commitment, and this study is expected to provide insights for companies in developing policies to improve employee performance.